PENGARUH STRATEGI PEMASARAN TERHADAP PENINGKATAN JUMLAH NASABAH DI PT. BPR ASWAJA PONOROGO - Yuniska Prasetyanti (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
The purpose of the research is (1) to know marketing strategy in PT. BPR Aswaja Ponorogo, (2) to know the improvement of the amount of client in PT. BPR Aswaja Ponorogo, (3) to know there is or do not it him influence of marketing strategy to make-up of the amount of client in PT. BPR Aswaja Ponorogo. The samples in this study using a sample of intended. The sample in this study is over 10 years old. Data collection using documentation and interviews to collect data marketing strategy and the number of customers in the PT. BPR Aswaja. Observation method is used to retrieve data marketing strategy. The data analysis technique used in this study is a simple linear regression analysis and the influence of different test. Result of research indicate that marketing strategy have influence at the same time relation which are positive to improvement of client amount in PT. BPR Aswaja Ponorogo. Matter  this means value of thitung > ttabel ( 3,524 > 1,859) hence refusing Ho with the meaning that there is influence between marketing strategy to make-up of the amount of client in PT. BPR Aswaja Ponorogo. Pursuant to research above, seen there is influence of marketing strategy to improvement of the amount of client in PT. BPR Aswaja Ponorogo.